Preparation of nitrate-selective porous magnetic resin and assessment of its performance in removing nitrate from groundwater. Issue 3 (1st February 2017) - Liu, Cheng; Zhu, Lifei; Zhang, Qian; Chen, Wei
ABSTRACT: Nitrate-selective, porous magnetic anion-exchange resin (NS-PMAER) with enhanced afﬁnity and higher selectivity for nitrate was synthesized, characterized and its performance in nitrate removal was investigated. The results show that NS-PMAER consists of spherical particles with an average size of 200 μm. It has mean pore diameter, total pore volume, and BET speciﬁc surface area of 21.38 nm, 0.3605 cm 3 /g, and 67.455 m 2 /g, respectively. The speciﬁc saturation magnetization of NS-PMAER was about 10.79 emu/g. Fourier transform infrared spectrometer (FTIR) and X-ray photoelectron spectroscopy (XPS) results indicate that NS-PMAER has selectivity for nitrate higher than that of MIEX® resin; its coefﬁcients of selectivity toward nitrate for nitrate and sulfate are 20.978 and 6.769, respectively, higher than those of MIEX® resin (1.256 and 4.342, respectively). Its working exchange capacity was 72.41 mg/mL. Column-exchange experiments' results suggest that it could be easily regenerated using 1.5 mol/L sodium chloride solution for a contact time of 30 min. Its recovery rate stayed at > 95% even after ﬁve rounds of recycling. Results of the pilot test indicate that NS-PMAER could effectively remove nitrate in groundwater, and ensure that nitrate concentrations of efﬂuent to meet the guideline limit for drinking water by the World Health Organization.